Assessment of a Shredding Technology of Waste Printed Circuit Boards in preparation for Ammonia-based Copper leaching - Prestele, Marc Patrick (Department of Chemical Engineering, 2021)
The electronic waste (e-waste) stream grows at a global annual rate of 3-5%, with an expected 50 Mt to be discarded worldwide in 2020 alone. These large amounts of e-waste pose considerable environmental and health problems while also presenting socio-economic opportunities to most nations, especially to developing countries such as South Africa. E-waste presents a specifically unique challenge to developing nations as they suffer the challenges associated with e-waste, but do not have sufficient waste volumes to adopt business models used in developed countries to harness the economic opportunities presented by the growth of this waste streams. Recycling of e-waste requires huge capital and operating costs to run integrated recycling facilities and developing countries generally lack this funding. Furthermore, developing countries suffer from inadequate infrastructure, absent legislation and lacking capital investment which are necessary for the processing of e-waste regardless of it being regarded as a secondary resource or waste. Printed circuit boards (PCBs) are a valuable fraction of e-waste, made up of tightly laminated metal-polymer composites containing several base and precious metals which makes them attractive to recyclers. Hydrometallurgy is a widely explored technology that allows for scalable operations for recovering metals from PCBs. However, for it to be effectively employed, the metals in PCBs need to be liberated or be accessible to leach agents. To date, this still heavily relies on energy-intensive pulverisation prior to the leaching and subsequent metal recovery stages. This paper explores the structure of the PCB, developing an understanding of how the structural design of the board translates to the difficulty in liberating or exposing the metals for leaching. The paper goes further to test and compare metal liberation techniques as well as compares energy consumption and costs associated with the techniques; with the view to identify a low energy and low capital investment method that would be suitable for adoption by small scale recyclers typical of those operating in South Africa. The structural design of the PCBs was explored through an intensive literature survey and conducting a case study of the PCB manufacturing process of a local company as well as running tensile tests, drop weight impact tests and three-point bending tests on a batch of custom-made PCBs supplied by the local company. The metal liberation methods tested included the use of an industrial grab shredder to size reduce and delaminate the PCBs, use of a planetary ball mill and some instances including precursors such as freezing the PCBs in liquid nitrogen or soaking the boards in NaOH to remove the upper- and lowermost epoxy layers. The effectiveness of each method was then evaluated using a diagnostic ammoniacal leach test in which the extent of copper dissolution from the PCB is used as an indicator of the performance of the liberation method. Results on the structural design of the PCBs showed that it would be suitable to use size reduction mechanisms that are based on impact stresses as the fibreglass and epoxy could absorb all other stresses at high intensity without failing. In general, all treated or untreated PCBs underwent a maximum of six shredding passes, with results generally producing poor recoveries, not exceeding 27.5%. “Untreated” PCBs, referring to PCBs that only have undergone shredding in the industrial grab shredder, showed increasingly iv higher copper recoveries with consecutively shredding cycles. The 6th cycle produced the highest copper recoveries of 6.80g (23.5%) after 72 hrs. PCBs that had been soaked in NaOH and undergone six passes through the industrial grab shredder recovered a maximum of 27.5%. Interestingly, using a similar process but only shredding the PCBs in four passes showed similar results at 26.14% Cu recovery. Shredding the PCBs in four passes and subsequently milling them for 60 min (without NaOH treatment) showed lower Cu recoveries at 13.29% and this was not improved by extending the milling time to 120 min. This showed that the NaOH treatment was more effective in exposing the outer layers of copper relative to the shredding and milling. It can be seen that apart from size reduction there is delamination of some of the shredded PCB pieces. However, this delamination is not always complete and Cu metal can still be seen covered by fibreglass and hence inaccessible to leach agents. It is concluded that the combination of the shredding and NaOH method has potential and it is recommended to incorporate a 2nd NaOH stage to further delaminate the inner layers of the PCB exposing the copper